The Marmet Technique as an Effort to Improve Breast Milk Production in Postpartum Mothers - Yuliandini, Astri; Ghita, Dwi; Azis, Reskiawati; Ani, Ani (Karya Kesehatan Siwalima, 2025)
The Marmet technique, which combines breast expression and massage, is designed to stimulate the breast milk ejection reflex. This method is believed to enhance the smooth flow of breast milk in postpartum mothers, but requires scientific validation. This study aimed to examine the effect of the Marmet technique on breastfeeding smoothness among postpartum mothers in the working area of the Watunohu Health Center, North Kolaka Regency. A quasi-experimental design with a two-group post-test only approach was employed. The study involved 32 postpartum mothers, divided into an intervention group (n=16) and a control group (n=16) through purposive sampling. The intervention group received the Marmet technique according to standard operating procedures (SOP), while the control group did not receive any treatment. Breastfeeding smoothness was assessed using a questionnaire covering eight indicators. Data were analyzed with the Mann-Whitney test, with a significance level set at p 0.05. On the fourth day postpartum, exclusive breastfeeding smoothness was achieved in 62.5% of mothers in the intervention group compared to only 18.8% in the control group. The Mann-Whitney test yielded a p-value of 0.017 (0.05), indicating a statistically significant effect of the Marmet technique. These findings demonstrate that the Marmet technique results in a significant increase in exclusive breastfeeding rates among postpartum mothers. It is recommended that healthcare providers in maternal and child health services adopt this technique as part of routine interventions to promote successful breastfeeding.